2020
DOI: 10.3390/cancers12103030
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Irradiation Induces Vascular Damage in the Aorta of Wild-Type Mice

Abstract: There has been a recent upsurge of interest in the effects of ionizing radiation exposure on the circulatory system, because a mounting body of epidemiological evidence suggests that irradiation induces cardio- and cerebrovascular disease at a much lower dose and lower dose rate than previously considered. The goal of our project is to determine whether dose protraction alters radiation effects on the circulatory system in a mouse model. To this end, the use of wild-type mice is pivotal albeit without manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Despite multiple studies investigating the health impacts of ionizing radiation, questions remain regarding the effects of exposure on cardiovascular diseases. Both epidemiological [1][2][3][4] and experimental studies [5][6][7][8][9][10][11] revealed that exposure to high doses of ionizing radiation has detrimental cardiovascular outcomes. However, when it comes to low dose ionizing radiation (LDIR), epidemiological studies have not provided a clear message.…”
Section: Introductionmentioning
confidence: 99%
“…Despite multiple studies investigating the health impacts of ionizing radiation, questions remain regarding the effects of exposure on cardiovascular diseases. Both epidemiological [1][2][3][4] and experimental studies [5][6][7][8][9][10][11] revealed that exposure to high doses of ionizing radiation has detrimental cardiovascular outcomes. However, when it comes to low dose ionizing radiation (LDIR), epidemiological studies have not provided a clear message.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a double-edged sword, downregulating angiogenesis and interrupting normal wound healing and bone defect repair. Numerous researchers have investigated radiation-associated vascular dysfunction and found that radiation causes endothelial cell apoptosis ( Paris et al, 2001 ), promotes structural disorganization and detachment of the aortic endothelium ( Hauer-Jensen, Fink & Wang, 2004 ), and enhances vascular permeability ( Hamada et al, 2020 ). However, the role the immune system plays in damaging the blood supply is rarely considered.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that patients receiving thoracic RT have an increased risk of coronary artery disease, valvular heart disease, congestive heart failure, pericardial disease and sudden death [17] and experimental studies have shown pre-lesion changes in the descending thoracic aorta of wild-type mice after total body irradiation (TBI, single acute exposure of 5Gy) [44]. It has been suggested that changes observed in the thoracic aorta following TBI could result not only from direct effects to the thoracic aorta but also from effects from various adjacent organs/tissues [44].…”
Section: Discussionmentioning
confidence: 99%